Strategi Dakwah Ustad Milenial dalam Membentuk Ketahanan Mental Generasi Muda di Desa Lasem Kecamatan Dukun Kabupaten Gresik - Rosedah Sa'datul Marwah; Sartikah Sartikah; Ani Khofiati (An-Nahdloh: Journal of Education and Islamic Studies, 2026)
The mental resilience of today's youth is a hot topic. During this period, adolescents experience numerous changes, both physically, mentally, and socially. In rural contexts, access to formal mental health services remains very limited, so religious figures such as Islamic scholars (ustadz) can play a significant role. Millennial Islamic scholars (ustadz) in the preaching space employ strategies that are more closely aligned with the digital culture and language of the younger generation, as rural youth are inextricably linked to media exposure and academic pressures. However, there is limited research describing how millennial Islamic scholars' preaching strategies realistically work to foster mental resilience in the rural context. The problem with this research lies in the lack of identification of the Islamic preaching strategies used by millennial Islamic scholars in conveying religious messages and the psychological and emotional aspects of the young generation. This case study, conducted in Lasem Village, Dukun District, Gresik Regency, aims to determine whether millennial Islamic scholars' preaching approaches are truly effective in fostering mental resilience. This research uses descriptive qualitative methods.  The research findings show that in fostering mental resilience in the younger generation in Lasem Village, millennial religious teachers (ustad) utilize a collaborative approach to preaching using three approaches: emotional, dialogical, and adaptive. The role of religious leaders is no longer limited to providing advice, but rather to being companions who can listen to the psychological experiences of the younger generation, validate their emotions, and convey Islamic values ​​in a light, contextual, and relevant language for everyday life. The implications of this research are that innovative approaches to preaching by religious leaders can be oriented toward both the religious dimension and measurable psychological empowerment.   Keywords: Youth, Mental Resilience, Da‘wah Strategies, Millennial Preachers